Inhibitory Effect of Diosgenin on Experimentally Induced Benign Prostatic Hyperplasia in Rats - 陈静 章怀奋 熊朝梅 阮金兰 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
This study investigated the effect of diosgenin,a natural sapogenin possessing various pharmacological activities,on benign prostatic hyperplasia（BPH） in rats and the possible mechanisms.BPH was established in the castrated rats by subcutaneous injection of testosterone propionate.Animals were randomly divided into four groups（n=10 each）：model group（0.5% sodium carboxymethyl cellulose）;positive control group（3 mg/kg finasteride）;two diosgenin groups（50 and 100 mg/kg）.The drugs were intragastricaly given in each group for consecutive 3 weeks.Another 10 rats with no testicles cut off served as negative controls and they were subcutaneously injected with 0.1 m L olive oil per day and then treated with 0.5% sodium carboxymethylcellulose.After 3-week administration,the prostate index and serum PSA level were determined,and histopathological examination was carried out.The levels of MDA,SOD and GPx in prostates were also measured.Additionally,the expression of Bcl-2,Bax and p53 was examined using Western blotting.The results showed that the prostate index and serum PSA level were significantly decreased,and the pathological changes of the prostate gland were greatly improved in diosgenin groups as compared with the model group.Elevated activities of SOD and GPx,and reduced MDA level were also observed in diosgenin-treated rats.In addition,the expression of Bcl-2 in prostates was down-regulated,whereas that of Bax and p53 was up-regulated in diosgenin-treated rats.These results indicated that diosgenin was effective in inhibiting testosterone propionate-induced prostate enlargement and may be a candidate agent for the treatment of BPH.